2017
DOI: 10.18203/2320-6012.ijrms20172122
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of treatment outcome in multi-drug resistant tuberculosis patients treated under programmatic conditions

Abstract: Background: Programmatic management of MDR-TB has taken over the un-standardized and unsupervised treatment practice in India. However, despite being implemented in whole of country, the data on the program surveillance is scarce.  Hence the present study was sought to evaluate the treatment outcome in patients with MDR TB in Chandigarh being treated under programmatic conditions.Methods: A retrospective study was carried out by enrolling all MDR-TB patients registered between January 2012 to December 2014. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
2
10
2
Order By: Relevance
“…In our study, the culture conversion rate was 87.7%, which was in accordance with previous studies reporting conversion rates ranging from 74% to 92%,[56181920212223242526] suggesting that adoption of the modified DOTS-Plus strategy might be a cost-effective strategy, particularly in high MDR-burden resource-limited setting like India. Reduction in culture examinations in the continuation phase can also help in diversion of available resources in further expansion of the existing program to cater to unmet populations.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the culture conversion rate was 87.7%, which was in accordance with previous studies reporting conversion rates ranging from 74% to 92%,[56181920212223242526] suggesting that adoption of the modified DOTS-Plus strategy might be a cost-effective strategy, particularly in high MDR-burden resource-limited setting like India. Reduction in culture examinations in the continuation phase can also help in diversion of available resources in further expansion of the existing program to cater to unmet populations.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of patients (78%) in this study had a sputum culture conversion at 6 months with median time of sputum smear and culture conversion at 3 months. A sputum culture conversion rate of 90% was achieved in our cohort which is higher than the conversion rates of 81.4% and 82.1% reported in two recent studies [25,26]. In spite of better Rwandan programme performance in term of successful outcome, high sputum/culture conversion and very low rates of treatment failure (0.6%) and loss to follow-up (0.6%), the rate of death among MDR-TB patients with unfavourable treatment outcome was an alarming finding of our study.…”
Section: Discussioncontrasting
confidence: 78%
“…[14][15][16] Majority of the cases (69.2%)were sputum positive retreatment cases which was in agreement with most of the other Indian studies and systematic reviews. [17][18][19] Sputum culture conversion at 3 rd month occurred in 56.7% of cases, which was low compared to other studies by Sachin S Dole et al and Deepak et al 12,13 But sputum culture conversion at end of 6 months was 83.9%, which was in agreement with other recent Indian studies, systematic reviews, and Meta-analysis.…”
Section: Discussionsupporting
confidence: 86%
“…In this study successful outcome was observed in 54.54%which was similar to a study done by Sachin S Dole et al, Sangita V. Patela et al study had a very low successful outcome (38.62%), and in a study by Deepak et al and in a systematic review of 36 studies the successful outcomes were 63% and 62% respectively. [11][12][13]18 In this study 21.6% of cases died which was in contrast to other studies ranging from 11% to 16.4 %. High death rate might be because of comorbidities and bilateral extensive i.e.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation